Endophytic Pestalotiopsis species associated with Rhododendron in Cangshan Mountain, Yunnan Province, China - Gu, Rui; Bao, Dan-Feng; Shen, Hong-Wei; Su, Xi-Jun; Li, Yun-Xia; Luo, Zong-Long (Frontiers in Microbiology, 2022)
Rhododendron is an essential ornamental plant, and Yunnan province is the genus's centre of diversity. In addition to endophytes, pathogens, and saprobes, Pestalotiopsis fungi are associated with a vast array of plant species worldwide. In this study, fresh leaves of Rhododendron decorum, R. delavayi, and R. cyanocarpum were collected from Cangshan Mountain, Yunnan Province, China, and Pestalotiopsis fungi were characterized using sequence data analyses of combined ITS, TEF1-α and TUB genes along with morphological characteristics. The result was the confirmation of seven species, of which six are described as new species. P. appendiculata, P. cangshanensis, P. daliensis, P. fusoidea, P. rosarioides and P. suae are introduced along with detailed descriptions and colour photo plates of these species (including a new host record for P. trachicarpicola).